Glandular trichome diversity on leaves of Lippia origanoides and Lippia stachyoides (Verbenaceae): morphology, histochemistry, and ultrastructure - Tozin, Luiz Ricardo dos Santos [UNESP]; Carvalho, Shelly Favorito [UNESP]; Machado, Silvia Rodrigues [UNESP]; Rodrigues, Tatiane Maria [UNESP] (Canadian Science Publishing, Nrc Research Press, 2015)
Despite the ecological and medicinal importance of glandular trichomes in Verbenaceae, information on their structure, mainly at the subcellular level, is sparse. We analyzed the morphology and histochemistry of glandular trichomes in Lippia origanoides Kunth and Lippia stachyoides Cham., using conventional methods in anatomy, histochemistry, scanning and transmission electron microscopy, and ultracytochemical techniques. Five morphotypes (I-V) of glandular trichomes were identified in L. origanoides, and four morphotypes (I, III-V) in L. stachyoides. Morphotype I is the most abundant in both species. Lipids were detected in all morphotypes except IV; terpenes in I, II, and V; phenolic compounds in all morphotypes except V; neutral polysaccharides and protein in all morphotypes; mucilage exclusively in IV; alkaloids only in III. Each glandular morphotype showed ultrastructural peculiarities compatible with the chemical compounds produced. An association between glandular morphotype, secretion composition, and ultrastructural features in Lippia species was revealed, suggesting functions specific to each glandular morphotype.
Keywords: Glandular trichomes; Histochemistry; Lippia; Secretion; Ultrastructure